Im not exactly sure how the square root of 1-(-1/3)/2 = the square root of 2/3?
Can someone explain this for me?
$\displaystyle \displaystyle \sqrt{\frac{1 - \left(-\frac{1}{3}\right)}{2}} = \sqrt{\frac{1 + \frac{1}{3}}{2}}$
$\displaystyle \displaystyle = \sqrt{\frac{\frac{4}{3}}{2}}$
$\displaystyle \displaystyle = \sqrt{\frac{4}{6}}$
$\displaystyle \displaystyle = \sqrt{\frac{2}{3}}$.
P.S. Please use brackets where they're needed, what you posted looks lke $\displaystyle \displaystyle 1 - \frac{\left(-\frac{1}{3}\right)}{2}$...